2015
DOI: 10.1167/iovs.15-17861
|View full text |Cite
|
Sign up to set email alerts
|

Active Maintenance of the Gradient of Refractive Index Is Required to Sustain the Optical Properties of the Lens

Abstract: Citation: Vaghefi E, Kim A, Donaldson PJ. Active maintenance of the gradient of refractive index is required to sustain the optical properties of the lens. Invest Ophthalmol Vis Sci. 2015;56:7195-7208. DOI:10.1167/ iovs.15-17861 PURPOSE. To determine whether the cellular physiology of the lens actively maintains the optical properties of the lens and whether inhibition of lens transport affects overall visual quality. METHODS.One lens from a pair of bovine lenses was cultured in artificial aqueous humor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 52 publications
2
58
2
Order By: Relevance
“…We have previously shown that Cx46fs380 distorts lens focusing, suggesting altered lens refraction (28). In cultured bovine lenses, inhibition of the lens circulation also alters the gradient of refractive index and lens optical properties (39). The gradient of refractive index in the lens depends on the radial gradient of protein concentration (33), which may relate to the lens intracellular hydrostatic pressure (15).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Cx46fs380 distorts lens focusing, suggesting altered lens refraction (28). In cultured bovine lenses, inhibition of the lens circulation also alters the gradient of refractive index and lens optical properties (39). The gradient of refractive index in the lens depends on the radial gradient of protein concentration (33), which may relate to the lens intracellular hydrostatic pressure (15).…”
Section: Discussionmentioning
confidence: 99%
“…The pressure gradient has a parabolic form reminiscent of the GRIN and indeed it has been suggested that the bulk flow of water may play a role in establishing the index gradient (Gao et al, 2013, 2015). In support of an active role for the lens microcirculation in generating and maintaining the GRIN, MRI imaging has been used to demonstrate that in the presence of high potassium solutions, low temperature, or ouabain (an inhibitor of the Na/K-ATPase), the water-protein gradient of the lens collapses and negative spherical aberration is reduced leading to reduced image quality (Vaghefi et al, 2011, 2015). On the basis of these findings it was concluded that the protein concentration gradients that underlie the GRIN are actively maintained through membrane-based processes.…”
Section: Mechanism Of Compactionmentioning
confidence: 99%
“…They are robust to variations of intracellular pressure. The evolutionary advantage of this adaptation is not clear to us, but may be more obvious to other workers with a greater knowledge of clinical realities that show how the lens becomes diseased [63,46,48,49]. Our simplified model suggests that all the quantities can be computed without knowing the intracellular pressure.…”
Section: Introductionmentioning
confidence: 99%